2005
DOI: 10.4049/jimmunol.175.5.2900
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mechanism by which IFN-γ Enhances Tumor Recognition: Active Release of Heat Shock Protein 72

Abstract: IFN-γ exhibits differential effects depending on the target and can induce cellular activation and enhance survival or mediate cell death via activation of apoptotic pathways. In this study, we demonstrate an alternative mechanism by which IFN-γ enhances tumor recognition, mediated by the active release of Hsp72. We demonstrate that stimulation of 4T1 breast adenocarcinoma cells and K562 erythroleukemic cells with IFN-γ triggers the cellular stress response, which results in the enhanced expression of total Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 64 publications
6
143
0
3
Order By: Relevance
“…Intracellular excess of Hsp70 supports its membrane trafficking upon heat stress -It has been shown that high temperature stress or heat analogue membrane fluidization could increase membrane concentration of Hsp70 [7,11,14,17,29,37]. To reveal whether and how the trafficking of Hsp70 changes in B16 cells upon heat stress we focused on the initial stages of stress response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular excess of Hsp70 supports its membrane trafficking upon heat stress -It has been shown that high temperature stress or heat analogue membrane fluidization could increase membrane concentration of Hsp70 [7,11,14,17,29,37]. To reveal whether and how the trafficking of Hsp70 changes in B16 cells upon heat stress we focused on the initial stages of stress response.…”
Section: Resultsmentioning
confidence: 99%
“…Membranebound Hsp70 on the tumor cell surface has been shown to trigger cytolytic attack by natural killer cells [10]. Moreover, intracellular Hsp70 was reported to be released from cancer cells [11][12][13][14][15][16][17]. Once released, extracellular Hsp70 exerts a dual, "chaperokine" function acting as a chaperone and a cytokine.…”
Section: Introductionmentioning
confidence: 99%
“…We have also previously reported that membrane Hsp70 + tumors actively release Hsp70 surface-positive lipid vesicles (25), which have the biophysical characteristics of exosomes (26,27) and that these can attract activated, but not resting NK cells. The current study found a significant increase in circulating Hsp70 in those mice in which tumor growth was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these involves the appearance of Hsp70 on the surface of certain tumor cells or virally infected cells, leading to phagocytosis and lysis of these cells [10,55,56,67,74,79]. New findings indicate that surface expression of Hsp70 on tumor cells is accompanied by Hsp70-release involving lipid rafts and exosomes and leading to an activation of natural killer (NK) cells also in the environment [3,6,33].…”
Section: Immuno−modulatory Effects Of Hsp70mentioning
confidence: 99%